2020
DOI: 10.1186/s12974-020-01762-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of astrocytes throughout life in wildtype and APP/PS1 mice after early-life stress exposure

Abstract: Background: Early-life stress (ES) is an emerging risk factor for later life development of Alzheimer's disease (AD). We have previously shown that ES modulates amyloid-beta pathology and the microglial response to it in the APPswe/PS1dE9 mouse model. Because astrocytes are key players in the pathogenesis of AD, we studied here if and how ES affects astrocytes in wildtype (WT) and APP/PS1 mice and how these relate to the previously reported amyloid pathology and microglial profile. Methods: We induced ES by li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 97 publications
(117 reference statements)
3
29
0
Order By: Relevance
“…Of course, these data do not preclude the possibility that ES might have modulatory effects at in-between as well as at later time-points, or how ES might interact with secondary “hits” that could alter the aging process. We and others have described how ES phenotypes are affected by challenges such as acute stress ( Bonapersona et al, 2019 ), diet ( Abbink et al, 2020b ; Ruigrok et al, 2021 ; Yam et al, 2017 ), and amyloid-β neuropathology ( Abbink et al, 2020a ; Hoeijmakers et al, 2017 , 2018a ), and it remains to be seen how these second hits might further alter the aging trajectory in the context of ES.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, these data do not preclude the possibility that ES might have modulatory effects at in-between as well as at later time-points, or how ES might interact with secondary “hits” that could alter the aging process. We and others have described how ES phenotypes are affected by challenges such as acute stress ( Bonapersona et al, 2019 ), diet ( Abbink et al, 2020b ; Ruigrok et al, 2021 ; Yam et al, 2017 ), and amyloid-β neuropathology ( Abbink et al, 2020a ; Hoeijmakers et al, 2017 , 2018a ), and it remains to be seen how these second hits might further alter the aging trajectory in the context of ES.…”
Section: Discussionmentioning
confidence: 99%
“…The potential involvement of ELA in AD has been studied in rodent models (Table 3 ). APPswe/PS1dE9 mice exposed to LBN displayed aggravated Aβ plaque load at 10 months of age accompanied by increased glial activation and inflammatory signals in the hippocampus [ 76 , 77 ]. LBN also increased the hippocampal levels of Aβ40 and Aβ42 and elevated the level of β-site APP-cleaving enzyme 1 (BACE1), a key rate-limiting enzyme for Aβ processing and production, in this mouse model [ 78 ].…”
Section: Main Textmentioning
confidence: 99%
“…For example, APP/PS1 mice show early elevated Aβ production and plaque formation in the hippocampus observed at 6 months of age (moa), which increases progressively with age [6]. In addition, these mice show synaptic dysfunction [7,8], presence of reactive astrocytes [9] and microglia [10], and multiple forms of memory impairments [8,11]. Studies have indicated synapse loss as early events in AD, which especially affect the hippocampus, and correlates with cognitive decline [3,12].…”
Section: Introductionmentioning
confidence: 99%